Investigating the cost and impact of water leakages in the Midrand region using the Economic Model for Leakage Management - Nsubuga, F.W.N. (Francis Wasswa Nkugwa) (University of Pretoria, 2020)
Dissertation (MSc (Environment and Society))--University of Pretoria, 2020.